An unusual finding after adrenal surgery: a case series of adrenal schwannomas - Kostek, Mehmet; Unlu, Mehmet Taner; Caliskan, Ozan; Aygun, Nurcihan; Iscan, Yalin; Dural, Ahmet Cem; Sormaz, Ismail Cem; Tunca, Fatih; Giles Senyurek, Yasemin; Uludag, Mehmet (Frontiers in Surgery, 2023)
Adrenal Schwannoma is a rare benign tumor that has no specific imaging and laboratory findings to diagnose preoperatively. Due to the limited number of cases in literature, clinical, imaging, and pathological findings are presented in this study. Case 1 is a 61-year-old female who has a 31 mm mass at right adrenal gland. This mass was non-functional and in imaging studies, this mass had a cystic necrotic component and high 18-fluorodeoxyglucose (FDG) uptake was seen. There was no metaiodobenzylguanidine (MIBG) uptake. Laparoscopic transabdominal right adrenalectomy was performed, and the pathology result was consistent with adrenal schwannoma. Case 2 is a 63-years-old male patient who presented with 38 mm mass in the left adrenal gland. This mass was non-functional and similar to Case 1, this mass had a cystic component. Laparoscopic transabdominal left adrenalectomy was performed. The diagnosis of adrenal schwannoma with degeneration was revealed. Case 3 was a 72-years-old female patient who was admitted to hospital for 125 mm left adrenal mass. Similar to Case 1, this mass was also presented with a cystic-necrotic component in imaging studies. High FDG uptake was seen and due to the suspicion of malignancy, the patient underwent conventional adrenalectomy. After pathological evaluation, a diagnosis of adrenal schwannoma was made. Main diagnostic challenge in adrenal schwannoma is the preoperative diagnosis. These masses have no pathognomonic finding or specific hormonal function. Imaging findings of these masses may increase the suspicion for malignancy, and this may affect decisions for surgery and surgical technique.